Pediatric tonsillar synovial sarcoma: extremely rare case report - Çalışkan Kamış, Şule; Yağcı, Begül (Frontiers in Pediatrics, 2025)
BackgroundSynovial sarcoma (SS) is a malignant tumor characterized by partial epithelial differentiation. While SS predominantly affects older children and young adults, it can arise in nearly any anatomical region. Its occurrence in the tonsil, particularly in the pediatric population, is extremely rare, with only one other case reported in the literature. This rarity poses diagnostic challenges, as its symptoms often resemble more common conditions such as a peritonsillar abscess. Reporting such cases is crucial to expanding the understanding of SS, refining diagnostic approaches, and guiding treatment strategies. This case offers valuable insights into the management of SS in atypical locations.Case presentationWe report the second documented case of pediatric tonsillar synovial sarcoma (SS). The patient, a 5-year-old girl, presented with a 1.5-month history of persistent fever and dysphagia. Radiological examinations revealed a mass originating from the right palatine tonsil, causing irregular narrowing of the oropharyngeal lumen, initially suspected to be a peritonsillar abscess. An incisional biopsy of the right tonsil was performed, and histopathological analysis confirmed the diagnosis of biphasic SS. The patient underwent six cycles of chemotherapy, resulting in significant tumor regression by the 6th month of treatment. This case underscores the necessity of a multidisciplinary approach, combining surgery and chemotherapy, in managing rare tumors.ConclusionsThis case highlights the importance of considering rare malignancies like synovial sarcoma in the differential diagnosis of atypical tonsillar masses, especially in pediatric patients with persistent symptoms. The successful outcome achieved through a multidisciplinary approach emphasizes the need for coordinated care in managing such complex tumors. This case contributes valuable insights to the limited literature on pediatric tonsillar SS and may guide future diagnostic and therapeutic strategies for similar cases.